Salmonella Dublin: a threat to dairy heifer survival and future performance - Schmidt, D.G.; Gnad, D.P.; Sargeant, J.M.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Salmonella dublin is a bacterium that can have devastating effects in dairy herds. It is most deadly with calves that range in age from 10 days to 5 months. Salmonella dublin is shed from carrier animals through feces, milk, and colostrum and spread by oral ingestion. Clinical signs are not detected easily until after the infection is well established. Calves may suffer from septicemia, diarrhea, fatigue, and unthriftiness. Death is not an uncommon outcome of this disease. Clinical signs of infection in adults may range from none to enteritis or abortion. Combating the disease requires an awareness of the disease, a preventive herd health program, and attention to detail in caring for the newborn calf.
Keywords: Dairy; Salmonella dublin; Heifers; Calves